Pengungkapan Laporan Keuangan Sebagai Variabel Mediasi Pengaruh Kualitas Corporate Governance Terhadap Asimetri Informasi - Laailatul Amanah; Nursiam Nursiam; Suhesti Ningsih (Jurnal Akuntansi dan Pajak, 2021)
The application of good corporate governance is a fundamental need for companies and other institutions to succeed in the long term, good governance will force companies to conduct sufficient financial statement disclosures so as to reduce information asymmetry for users of financial statements. This study aims to examine whether quality of corporate governance influences information asymmetry through disclosure of financial statements. The object of this study is a non-financial category compannies that has obtained a score related to the implementation of corporate governance by IICG which was published in SWA magazine as the Most Trusted Conpany from 2012 to 2018. The sample selection process uses purposive sampling. The results of sample selection were obtained by 52 companies The data analysis technique in this study uses path analysis. The test of the direct effect of quality of corporate governance on information asymmetry shows that corporate governance quality has a positive effect on information asymmetry, while the test results of the indirect effect of corporate governance quality on information asymmetry through financial statement disclosure show that disclosure of financial statements is not a mediating variable on the effect of corporate governance quality on information asymmetry, this is caused because almost all sample companies make disclosures of financial statements in a relatively the same amount but the CG score results change in each year.